STUDY OF THE EFFECT OF HALOTHANE ON THE LIVER - H. Morcus, N.; H. Dawood, W.; Shnain, H. (The Iraqi Journal of Veterinary Medicine, 1989)
Halothane effect on the liver of rabbits have been studied. Rabbits were aneasthetized with halothane for 15, 30, 45 and 60 minutes. Anesthesia was repeated at the second and third day for same of them. Other animals were anesthetized with ether for the same periods while another group was exposed for oxygen in these same system. ALT enzyme have been measured before and after anestesia for all groups. Gradual increase of ALT enzyme has been observed with the increase in time within the same period of exposure but it was not significant.